Effect of the insecticide Metamidofos on the germination, growth and entomopathogenic activity of Beauveria bassiana - Milagros del Socorro Fenco-Villanueva (2017)
The effect of the 1200 and 1800 ppm concentrations of the insecticide metamidofos on the germination, growth and entomopathogenic activity of Beauveria bassiana was determined. The effect on B. bassiana germination was determined by placing 2mL of each insecticide concentration in small flasks, adding 2mL of the conidia suspension, to obtain a final concentration of 1x105 conidia/mL It was incubated at temperature of 25 ° C for 24 hours, then counted germinated conidia. For growth, the insecticide was incorporated into potato dextrose agar, and served in Petri dishes, as well as a control plate containing only culture medium, by puncturing in the central part of each Petri dish according to its corresponding concentration of each insecticide and the control, incubating at 25 ° C for 7 days. For the entomopathogenic activity S. frugiperda larvae were inoculated with the fungus grown in the media with the insecticide at the two concentrations worked, a control was also inoculated, which consisted of inoculating the larvae with the fungus grown on potato dextrose agar. It was found that metamidofos significantly decreases the in vitro germination of B. bassiana at 1200 ppm and 1800 ppm, but does not significantly decrease growth. As for the entomopathogenic capacity it was found that metamidofos does not affect the pathogenicity of B. bassiana on S. frugiperda larvae. It is concluded that the insecticide metamidofos lowers the percentage of B. bassiana germination at the concentrations of 1200 ppm and 1800 ppm, but does not affect the growth rate and entomopathogenic activity of this fungus.